2022
DOI: 10.1515/jpem-2022-0076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of insulin sensitivity indices for detection of double diabetes in Indian adolescents with type 1 diabetes

Abstract: Objectives The role of insulin sensitivity (IS) in the development and progression of metabolic syndrome (MS) in subjects with type-1 diabetes (T1D) is being increasingly recognized. As patients with T1D lack endogenous insulin secretion, measurement of insulin concentration by immunoassay or by indices such as homeostasis model of assessment for insulin resistance (HOMA-IR) is not helpful in assessing IS. Hence, some equations have been developed and validated against data from euglycemic-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…We thus concluded that Metformin may prevent deterioration in IS in Indian adolescents with T1D. 76 In T1DM, the favorable effects of Metformin are not only restricted to the reduction of insulin resistance but also to the reversal of micro and macrovascular complications when diagnosed sufficiently early. In a study by Pena et al on adolescents with T1DM, a significant association between early signs of atherosclerosis (as evidenced from cIMT) and retinal microvascular changes was observed irrespective of age, gender, HbA1c and blood pressure.…”
Section: Metformin Adjunct Therapymentioning
confidence: 79%
See 1 more Smart Citation
“…We thus concluded that Metformin may prevent deterioration in IS in Indian adolescents with T1D. 76 In T1DM, the favorable effects of Metformin are not only restricted to the reduction of insulin resistance but also to the reversal of micro and macrovascular complications when diagnosed sufficiently early. In a study by Pena et al on adolescents with T1DM, a significant association between early signs of atherosclerosis (as evidenced from cIMT) and retinal microvascular changes was observed irrespective of age, gender, HbA1c and blood pressure.…”
Section: Metformin Adjunct Therapymentioning
confidence: 79%
“…8,[38][39][40] The author's group in a study on subjects from their center found that IS by SEARCH equation had highest accuracy in identifying IR and hence proposed its use in clinical practice in adolescents with T1DM at risk of developing metabolic as well as microvascular complications. 41…”
Section: Insulin Sensitivity Prediction Equationsmentioning
confidence: 99%
“…The increase in weight in T1DM could be explained by the intensive use and high doses of exogenous insulin therapy in the management of T1DM which in turn has an anabolic effect on lipid metabolism thus promoting lipogenesis and weight gain. Moreover, insulin resistance may develop in T1DM especially with onset of puberty and long duration of the disease with characteristic abdominal obesity and liability for development of metabolic syndrome (17,18) . As regards the clinical and laboratory findings, serum levels of cholesterol, triglyceride, LDL-C and CRP were significantly higher in patients group than controls.…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies comparing indirect insulin resistance markers are incoherent and it is impossible to indicate at the moment which marker is better than others [ 71 , 81 , 122 ]. Moreover, the specific cut-points of different insulin resistance markers for IR and/or MS detection may vary depending on the ethnicity and the statistical methods used in studies.…”
Section: Recognition Of Double Diabetes—the Role Of Indirect Insulin ...mentioning
confidence: 99%